Examining information needs of public data service users: a study based on the ‘Message Board for Leaders of People’s Daily in China’ - Zhang, Xiaoyue; Liu, Jinya; Wang, Xinyue; Ma, Wanteng; Yan, Pu (Information Research an international electronic journal, 2024)
Introduction. Governance process optimisation is critical to achieve the goal of improving public services efficiency. Public data service is crucial starting point for realising this goal. However, practical challenges persist in public data service, including unclear processes and insufficient identification of public data service citizens’ information needs. Method & Analysis. We employed an inductive methodology to analyse the public data service users’ information needs and annual distribution among information needs. Based on a data-driven approach, we mapped these information needs sub-categories into four main procedures in public data service. This paper further identified the hierarchy of information needs based on public data processing levels. We utilised Sankey diagram to effectively illustrate cross-analysis result between topics and information needs’ subcategories. Results. The typical levels of public data service users’ information needs include informing, utilisation, problem-solving, social life service, and society governance. Furthermore, our study reveals the data flow among sub-categories of public data service information needs follows the logic of Datafication- Government to Government-Government to citizens- Data to Optimiation. Conclusion. Government departments should ensure public data quality and facilitate efficient data circulation processes. We recommend understanding relationships between public data resources and services derived from them through a problem-solving lens. Our findings will serve as a reference tool for analysing information needs of public data service users in other countries.